Influence of Social Media Marketing in Development of Customer Trust and Satisfaction through the Moderating Role of Electronic Word of Mouth (Journal of Social Sciences Review, 2023)
The study's objectives were to inspect how media marketing influenced the development of customer satisfaction and trust through the mediating effect of consumer engagement. In Pakistan, a quantitative study was conducted to solve this problem. The core data for the research was gathered by a questionnaire from a sample group of around 310 persons, covering government employees, private sector workers, company executives, and students. The proposed framework under this study extracts the empirical stats using SPSS like demographics, reliability, descriptive statistics and correlation. Confirmatory Factor Analysis assessed the accuracy and effectiveness of the model and SEM-Structured Equation Model technique applied to the suggested model using SmartPLS 4. The findings revealed a significant positive association among factors of social media marketing, rewards, brand image, electronic word of mouth, customer engagement, customer trust and satisfaction. At the end of this study, limits and future implications are discussed, as well as practical and theoretical ramifications.
Keywords: Social Media Marketing; Rewards; Brand Image; Consumer Engagement; Customer Trust; Customer Satisfaction